UTILITARIANISM AND THE AIMS AND OBJECTIVES OF ADULT EDUCATION (1991)
Much of what has been said and written on educational aims has been prescriptive; it has asserted not what they are, but what they should be. That happiness has been prescribed indicates that it is an ideal, which finds expression in a natural phenomenon. Because of its natural and comforting illusions, aims such as this carry a persuasive force of positive connotations which encourages varieties of hyperbolically optimistic assumptions about its effects, in order to avoid these assumptions becoming unchallenged fashionable ideas in educational arena, particularly in the realm of adult education, the need for a careful scrutiny arises. Thus in prescribing Utilitarianism as an aim for adult education.; this study has examined the following issues: (1) The meaning of aims and the justification for the formulation of aims in adult education; (2) Some philosophical theories that form the basis of the aims and objectives of adult education; (3) utilitarianism and education; (4) utilitarianism as an aim of adult education; and (5) Problems associated with the achievement of Utilitarianism in adult education. The above examination was carried out using the instrument of philosophical analysis in the following manner: First, major concepts were picked out for analysis in order to understand the principles by which their uses are determined. Thereafter, some crucial themes subjected to critical analysis so as to eliminate psuedo-problems that are likely to arise at the practice and implementation stages. This led to the clarification of the underlying basic assumptions arising there from, so as to put the real issue in clear perspective. Later, a synthesis of all the positive ideas highlighted in the process of our critical analysis of concepts and issues on the topic was drawn together. The result of this exercise was the restatement of the theory of happiness in the context of adult education. Finally, counter-objections to the new statement was raised in the form of unbiased criticism and answers were provided for such objections. The reason for this task is to dig up any ambiguity that may be hidden in the new formulation. It was found out that Utilitarianism is made up of very many component parts of ethical theories that renders it almost an impossible target to be aimed at. The problem with utilitarian doctrine is that it obscures the identification of appropriate goals and standards of achievement in the education of adults. However, the utilitarian doctrine sees man as primarily concerned with the pursuit of happiness and as such regards the maximisation of happiness and the minimisation of suffering as the supreme of social action. Thus, the promise of a psychological well-being as is contained in the utilitarian doctrine is enough a factor that can attract political as well as Our conceptual analysis reveals it as a system of social economic and academic attention and political decision, as offering a criterion and basis of judgement for administrators as well as a system of personal morality. It is claimed that freedom of thought, autonomous decision making and truth are important elements for human happiness. Without freedom, there can be no genuine interaction with environment, no willing involvement in the life of society; and participation will become an irksome imposition, pedagogically, this points to an education oN, involvement, of participation, of activity and an education that involves discovery. Epistemologically, what is to be known and learnt is to be derived from the data of the product of the learner's experience. As such, it is argued that education should not be seen as the privilege of a few, but as the right and the obligation of all. If this is to be achieved, the government has to restructure its present role concerning adult education. It is therefore recommended that adequate financial provision should be made available for the establishment of adult centres for learning. Adult learning calls for distinct methods; as such, efforts should be made to train adult teachers, and access to the adult centres should be based on individual’s interest and not on government selection and finally, the curriculum of the centres should be structured in such a manner as to focus on the well-being of the learners.